IMPLEMENTATION OF TRANSPARENT AND ACCOUNTABLE PRINCIPLES IN SCHOOL FINANCIAL MANAGEMENT - Kurniasari, Putri; Rindani, Adia; Wulandary, Selly; Andriesgo, Johan; Nadialiana; Ramdani; Rasyidi, Arya (International Journal of Multidisciplinary Reseach, 2025)
Transparent and accountable school financial administration supports the smooth running of education programs. Through proper planning, recording, and reporting, funds are used efficiently and prevent misuse. This principle is important to improve the quality of education, achieve educational goals, and involve stakeholders in the supervision and evaluation of school financial management. The discussion uses a qualitative approach with a literature analysis method. Data were collected from various documents such as books, journals, notes, and digital sources. After collection, a content analysis was carried out on the data, including understanding, explanation, and conclusions, with reference to information from writings, recordings, and images related to the research. School financial transparency means openness of information on the use of funds that is clear and accessible to all parties, building trust and ensuring fairness. Accountability is the responsibility of the institution in managing funds according to plans and regulations. This openness encourages community participation and trust, in accordance with the principles of fairness, efficiency, and public accountability. Transparency and accountability in school financial management are important to build trust and ensure efficient use of funds. Through open reporting, internal supervision, and community and school committee involvement, fund management becomes fair and responsible, supporting the achievement of quality education and effective and sustainable financial governance.